2009
DOI: 10.1093/jxb/erp112
|View full text |Cite
|
Sign up to set email alerts
|

The impact of blue light on leaf mesophyll conductance

Abstract: Blue light has many direct and indirect effects on photosynthesis. The impact of blue light on mesophyll conductance (g(m)), one of the main diffusive limitation to photosynthesis, was investigated in leaves of Nicotiana tabacum and Platanus orientalis, characterized by high and low g(m), respectively. Leaves were exposed to blue light fractions between 0% and 80% of incident light intensity (300 micromol photons m(-2) s(-1)), the other fraction being supplied as red light. Leaves exposed to blue light showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
88
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 20 publications
15
88
0
2
Order By: Relevance
“…Additionally, they could found no difference in the distance between the centers of the chloroplasts and the closest air spaces between two samples (Gorton et al, 2003). Another group found that blue light rapidly reduced CO 2 diffusion from intercellular air spaces to the chloroplasts in both Nicotiana and Platanus leaves and that this reduction was completed before chloroplasts finished the avoidance movement to the aniticlinal walls (Loreto et al, 2009). Importantly, the blue-lightinduced reduction of CO 2 diffusion was still normal in samples treated with an anti-actin inhibitor cytochalasin, which completely inhibits chloroplast movement (Loreto et al, 2009).…”
Section: Influence Of the Chloroplast Avoidance Response On Co 2 Diffmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, they could found no difference in the distance between the centers of the chloroplasts and the closest air spaces between two samples (Gorton et al, 2003). Another group found that blue light rapidly reduced CO 2 diffusion from intercellular air spaces to the chloroplasts in both Nicotiana and Platanus leaves and that this reduction was completed before chloroplasts finished the avoidance movement to the aniticlinal walls (Loreto et al, 2009). Importantly, the blue-lightinduced reduction of CO 2 diffusion was still normal in samples treated with an anti-actin inhibitor cytochalasin, which completely inhibits chloroplast movement (Loreto et al, 2009).…”
Section: Influence Of the Chloroplast Avoidance Response On Co 2 Diffmentioning
confidence: 99%
“…Senn (1908) hypothesized that this positioning might result from the chemotaxis of chloroplasts to the CO 2 in air spaces. Using different approaches and plant species, three groups examined whether chloroplast photorelocation movement, especially the avoidance response, influenced CO 2 diffusion in leaves (Gorton et al, 2003;Loreto et al, 2009;Tholen et al, 2008). One research group hypothesized that chloroplast distribution on the anticlinal walls by the avoidance response facilitated CO 2 utilization by shortening the CO 2 diffusion path length from air spaces to the mesophyll chloroplasts (Gorton et al, 2003).…”
Section: Influence Of the Chloroplast Avoidance Response On Co 2 Diffmentioning
confidence: 99%
See 3 more Smart Citations